Ghostly reunion - Kappes, Tonya (Kappes, Tonya. Ghostly southern mystery., 2016)
Proprietor of the Eternal Slumber Funeral Home, Emma Lee can see, hear, and talk to ghosts of murdered folks. And when her high school nemesis is found dead, Jade Lee Peel is the same old mean girl trying to come between Emma Lee and her hot boyfriend, Sheriff Jack Henry Ross, all over again. There's only one way for Emma Lee to be free of the trash-talking ghost- solve the murder so the former prom queen can cross over. But the last thing Jade Lee wants is to leave the town where she had her glory days.